2019
DOI: 10.24198/pjd.vol31no1.21154
|View full text |Cite
|
Sign up to set email alerts
|

Changes in soft tissue facial profile of class II skeletal malocclusion patients with retrognathic mandible treated with twin block appliance

Abstract: Introduction: The soft tissue aspect in orthodontics treatment has gained attention in the last few years. The soft tissue profile is said to reflect the underlying skeletal profile, which causes a convex profile in patients with class II skeletal malocclusion. This research was aimed to determine the changes in the soft tissue facial profile of class II skeletal malocclusion patients with retrognathic mandible after twin block treatment. Methods: The type of research used in this study was retrospective descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…It consists of acrylic bite blocks on the upper and lower jaw that interlock at a 70-degree angle to guide the mandible downward and forward. ( Lin et al, 2019 , Zhang et al, 2020 ) Children with a considerable overjet and class II malocclusion benefit the most from it, even at an early stage of development, as functional devices like twin blocks can be utilized. ( Chen et al, 2022 , Golfeshan et al, 2018 , DiBiase and Qureshi, 2020 ) Ajami S et al stated that twin blocks have the potential to impact the class II malocclusion patients' facial aesthetics by causing modifications to the skeletal and dentoalveolar structures.…”
Section: Discussionmentioning
confidence: 99%
“…It consists of acrylic bite blocks on the upper and lower jaw that interlock at a 70-degree angle to guide the mandible downward and forward. ( Lin et al, 2019 , Zhang et al, 2020 ) Children with a considerable overjet and class II malocclusion benefit the most from it, even at an early stage of development, as functional devices like twin blocks can be utilized. ( Chen et al, 2022 , Golfeshan et al, 2018 , DiBiase and Qureshi, 2020 ) Ajami S et al stated that twin blocks have the potential to impact the class II malocclusion patients' facial aesthetics by causing modifications to the skeletal and dentoalveolar structures.…”
Section: Discussionmentioning
confidence: 99%
“…The ideal indication for a skeletal Class II malocclusion with a retrognathic mandible is a functional appliance. (18) Functional appliances have been used for many years in the treatment of Class II malocclusions with the aim of obtaining bone correction of the malocclusion. The use of these appliances should support an increase in the position and growth of the mandible along with changes in the tooth-muscle relationship.…”
Section: Reduction Of the Duration Of Subsequent Phase II Treatmentmentioning
confidence: 99%
“…The design that is separated into two parts, the top and bottom on this appliance provides convenience in speaking and chewing. (16,18) A clinical trial has shown that class II malocclusion can be corrected with an activator device. It has been reported that maxillary growth can be limited by the use of an activator.…”
Section: Introductionmentioning
confidence: 99%
“…7 For example, class II skeletal malocclusion with a protrusive maxilla may produce a convex facial profile, while class III skeletal malocclusion with a protrusive mandible may result in a concave facial profile. 8,9 Convex, concave, and straight soft tissue profiles can help determine the underlying skeletal relationship and position of the jaws from the sagittal plane. 10 According to Kasai, the relationship between facial soft tissue and skeletal structures may vary because soft tissues can be affected by thickness, function, and length.…”
Section: Introductionmentioning
confidence: 99%